A NOVEL INTEGRON IN THE GENOME OF ESCHERICHIA COLI ISOLATED FROM INDONESIAN MONITOR LIZARD (VARANUS SPP). - ESTI PUSPITASARI; ANTONIUS SUWANTO; AMARILA MALIK; WALTER ERDELEN (SEAMEO BIOTROP, 2001)
The genotype of antibiotic resistance in natural isolates of Escherichia coli was determined through integron detection and characterization of the associated antibiotic resistance. E. coli SG2 isolated from Varanus salvator of Java demonstrated resistance to spectinomycin (50ng/ml) and streptomycin (SOng/ml). Integron detection indicated that eight isolates out of nine E. coli isolates possessed a conserved segment of the integron. Amplification of the inserted cassette of the integron in this SG2 isolate yielded a 1-kb DNA fragment. Sequence analyses indicated that this fragment was homologous with aad gene, which confirmed the resistance to spectinomycin/streptomycin. This is the first report on the presence of integron in the E. coli isolated from the environment. Key words: Integron / antibiotic resistance / Escherichia coli